The method of integration of silicon – micromachined sensors and actuators to microreactor made of Foturan® glass - Knapkiewicz, Paweł; Walczak, Rafał; Dziuban, Jan A. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2007)
In this article results of unique low temperature anodic bonding silicon and Foturan® glass are presented. The new method of anodic bonding can be useful in designing and fabrication of intelligent microreactors equipped with microsensors and other microdevices suitable both to control and to steer chemical process. Direct assembling onto microreactors allows to think about integrated microreactors equipped with set of sensors, i.e., pressure sensors and other devices, i.e., valves, flow meters, etc. The demand for integration microreactor with measuring /steering setup, following the technology of low temperature anodic bonding and application of this technique are described.
Optica Applicata, Vol. 37, 2007, nr 1-2, s. 65-72
Keywords: optyka; microreaction technology; sensors integration; low temperature anodic bonding; Foturan® glass and silicon anodic bonding